Study on quality parameters of grapes (Vitis vinifera) and raisins affected by grape type - somkuwar, R G; Snehalkad, Snehalkad; Naik, S; Sharma, Ajay Kumar; Bhange, M A; Bhongale, A K (The Indian Journal of Agricultural Sciences, 2020)
Grape (Vitis vinifera L.) is one of the most important fruit crops of the country well known for health benefits. Varietal variations are recorded in quality of grapes and processed products. In present study 10 grape varieties (white seedless and colour seeded) were evaluated for properties of grapes and raisins. Bigger bunches were recorded in H-27 and closely followed by Manjari Naveen while maximum weight of 10 berries was observed in E8-5. Among these higher TSS was recorded in Manjari Kishmish (22.40Â°B) while Manjari Naveen variety was noted with minimum TSS (18.13Â°B). Raisin recovery was ranged from 22.88% in H-27 to 26.40% in Manjari Kishmish. Weight of 50 raisins was maximum in Carolina Blackrose (50.38 g) while Thompson Seedless was registered with minimum weight of 50 raisins. Raisins obtained from Kishmish Moldoski contained maximum reducing sugar (55.43 g/100 g) followed by Black Maladein (51.04 g/100g) while minimum reducing content in was recorded in raisins from Gulabi (31.93 g/100 g). Raisins from Manjari Kishmish contained higher protein (43.94 mg/g) and same raisins were found with maximum carbohydrate content (776.43 mg/g). Raisins obtained from grapes of H17 contained higher values of phenols and anthocyanins. Sensory studies showed that raisins obtained from Thompson Seedless scored maximum for overall acceptability while Carolina Blackrose was favored for color. Raisins of Manjari Naveen were found flavor and appreciated.